Corporate ESG Profiles and Banking Relationships. (23rd November 2021) - Houston, Joel F; Shan, Hongyu
Abstract: We show that banking relationships promote corporate environmental, social, and governance (ESG) policies. Specifically, banks are more likely to grant loans to borrowers with ESG profiles similar to their own and positively influence the borrower's subsequent ESG performance. Their influence is more pronounced when (1) banks have significantly better ESG ratings than borrowers and (2) borrowers are bank dependent. We exploit M&A among lenders as a source of quasi-exogenous variation in the lender's ESG standard to alleviate endogeneity concerns. Overall, our study presents the first evidence on the interplay between responsible bank lending and borrowers' ESG behavior.